2020
DOI: 10.1186/s40842-020-00094-4
|View full text |Cite
|
Sign up to set email alerts
|

A challenging case of Mesenchymal Chondrosarcoma involving the thyroid and special considerations for diagnosis

Abstract: Background: Thyroid ultrasound is usually used to risk-stratify incidental thyroid nodules. Nodules with high risk sonographic features for malignancy are evaluated by fine-needle aspiration. The role of core needle biopsy for thyroid nodules is limited to cases where the fine needle aspiration is inconclusive. Case presentation: We describe a rare case of mesenchymal chondrosarcoma of the thyroid gland with uncertain primary origin. Thyroid ultrasound showed right sided large, solid, hypoechoic nodule with ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Conventional chondrosarcomas can be graded grade I, II, or III depending on nuclear size, differentiation, and cellular density [9]. Both primary and metastatic chondrosarcoma of the thyroid are rarely reported in literature with only a few cases previously reported [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional chondrosarcomas can be graded grade I, II, or III depending on nuclear size, differentiation, and cellular density [9]. Both primary and metastatic chondrosarcoma of the thyroid are rarely reported in literature with only a few cases previously reported [10].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, primary thyroid chondrosarcoma was only reported once in literature when Abbas et al reported a case of extraskeletal mesenchymal chondrosarcoma of the thyroid gland in a 13-year-old female [6,7]. Interestingly, earlier reports about primary chondrosarcoma in elderly males were described by Jasonni et al, Tselini-Balafouta et al, and Haeri et al, while the most recent report of a 24-year-old Asian male with mesenchymal chondrosarcoma of the thyroid gland with uncertain primary was by Nachawi et al in 2020 [10][11][12][13]. Thyroid metastases from chondrosarcoma were also rarely reported in literature.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been discovered such cases as of dumbbell-shaped intramedullary MCS with isolated punctate calcification (only 7 cases of this type have been described since 1978) [ 15 ], secondary pancreatic MCS (a total of 13 cases have been reported) [ 4 ], primary renal EMC (only 16 patients with renal EMC have been described) [ 14 ], primary orbital intraocular MCS (40 cases reported in the literature) [ 16 ], and secondary thyroid MCS (only one case of this metastases has been reported in the literature) [ 17 ]. Nevertheless, MCS commonly present as large masses (>10 cm) and often present with chondroid calcifications (80%).…”
Section: Chondrosarcoma Diagnosticsmentioning
confidence: 99%